Maternal Thyroid Hormone Deficiency During Gestation and Lactation Alters Metabolic and Thyroid Programming of the Offspring in the Adult Stage - Tapia-Martínez, Jorge; Torres-Manzo, Alejandra Paola; Franco-Colín, Margarita; Pineda-Reynoso, Marisol; Cano-Europa, Edgar (Hormone and Metabolic Research, 2019)
Environmental stimuli during critical developmental stages establish long-term physiological and structural patterns that “program” health during adult life. Little is known about how alterations in hormonal supply might have consequences in metabolic and thyroid programming. This work aims to prove that alterations in the supply of thyroid hormones during gestation and lactation have long-term consequences in the metabolic and thyroid programming of the offspring. Female Wistar rats were divided into euthyroid, hypothyroid, and hypothyroid with 20 μg/day of s.c. thyroxine (T4), replacement wet nurses. Rats were mating, and after birth, pups were grouped according to their wet nurses group. Milk quality of wet nurses was assessed on days 7, 14, and 21. Body mass gain and energy intake of the offspring were monitored for 28 weeks after weaning. At sacrifice, we extracted and weighed their thyroid gland and adipose reserves, and collected blood to measure its metabolic and thyroid profiles. Hypothyroid wet nurses presented a persistent low quality of milk, while both male and female hypothyroid offspring presented lower body mass gain, higher blood glucose, dyslipidemia, hyperinsulinemia, and hyperleptinemia, as well as lower total adipose reserves, but higher visceral reserve, diminished T3 and T4 concentrations, and lower weight of thyroid gland. Thyroxine replacement prevented all changes in both wet nurses and pups. We conclude that maternal thyroid hormone deficiency during congenital and lactation stages alters the metabolic and thyroid programming of the offspring, while the reestablishment of maternal thyroid status during critical periods of development can prevent these alterations.
Keywords: thyroid hormone; congenital hypothyroidism; metabolic programming; thyroid programming; hormonal replacement